PENGARUH PENGAWASAN PIMPINAN TERHADAP KINERJA PEGAWAI PEMUNGUT RETRIBUSI PELAYANAN PASAR DI PASAR PARUNGKUDA KABUPATEN SUKABUMI - Dede Riansyah; Hamzah Jamaludin; Enyang Krismon (Mimbar Administrasi Mandiri, 2024)
The research found several indications of problems regarding the performance of market service levy collector employees, these are indicated as follows: 1) The predetermined market service levy revenue target has not been achieved. 2) lack of outreach to traders regarding the levy rates that must be paid. 3) The collection process and mechanism are not yet optimal. 4) Lack of responsiveness and follow-up from collection staff regarding problems in the field. On the Performance of Market Service Levy Collectors at Parungkuda Market. Researchers use Supervision theory (Vx) according to Winardi (2011:589) in Sururama and Amalia (2020:70. and Performance theory (Vy) according to Mangkunegara (2021:67). The approach used is quantitative. Meanwhile, the method used is the associative descriptive survey method. The data collection techniques used in this research were observation, interviews and questionnaires with a rating scale of five (5) answer choices. In sampling, Proportionate stratified random sampling and Purposive sampling techniques were used, and sample determination was used using the Slovin formula. The calculation result of the cumulative average value of the Leadership Supervision variable (Vx) is 3.98. Descriptive Percentage (DP) of 79.60% is included in the "Good" category. And Employee Performance (Vy) is 3.57. Descriptive Percentage (DP) =71.31% is included in the "Good" category. The results of statistical analysis Rxy = 0.785 are included in the "Strong" category. KD value = 0.61.6, which means that the contribution of the Leadership Supervision variable to Employee Performance is 61.62%, the remainder is determined by other factors. The linear regression equation obtained is Ŷ = 12.411 + 0860.